2013
DOI: 10.4322/rca.2013.012
|View full text |Cite
|
Sign up to set email alerts
|

Doses crescentes de gesso agrícola, estabilidade de agregados e carbono orgânico em Latossolo do Cerrado sob Cafeicultura

Abstract: The management of perennial crops could encourage the improvement of the soil, making it more productive, provided that appropriate agronomic practices are adopted. In order to evaluate the structure of a Cerrado Latosol subjected to soil management that adopts the use of high doses of gypsum and brachiaria on the coffee plants interrow, we studied the stability of aggregates and total soil organic carbon after two years of deployment of coffee. Soil samples were collected at 5 and 15 cm of depth in the crop c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 12 publications
3
8
0
18
Order By: Relevance
“…Nevertheless, it is truly observed an influence of OM on the DF, which decreases with OM reduction (ROSA JUNIOR et al, 2006). Table 2 also shows a GMD increment that followed the sequence: NV > P > NT, corroborating Silva et al (2013Silva et al ( , 2006 results. Lack of human interference and elevated OM content in NV might be possible explanations for GMD increase (Table 3).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, it is truly observed an influence of OM on the DF, which decreases with OM reduction (ROSA JUNIOR et al, 2006). Table 2 also shows a GMD increment that followed the sequence: NV > P > NT, corroborating Silva et al (2013Silva et al ( , 2006 results. Lack of human interference and elevated OM content in NV might be possible explanations for GMD increase (Table 3).…”
Section: Resultssupporting
confidence: 72%
“…Therefore, knowing soil structural quality and its variation throughout the time is crucial to predict such effects (VIANA et al, 2004). This way, several researches have been carried out to draw structural quality indexes by monitoring the effects of management practices on soil physical, chemical, water and biological attributes (BERGAMIN et al, 2010;LIMA et al, 2012;OLIVEIRA et al, 2004;SEVERIANO et al, 2009); besides organic matter dynamic along its profile (COSTA JUNIOR et al, 2012;SILVA et al, 2013;TIRLONI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(Costa Júnior et al 2012), which was also observed by Silva et al (2013) at a depth of 0.15 m in G7, working in the same area of this experimental research. The formation and stability of macro-and microaggregates, which influence the distribution of space voids is strongly related primarily to the oxidic mineralogy and clay texture.…”
Section: Treatmentssupporting
confidence: 73%
“…Ciênc. Agrotec., Lavras, v.38, n.5, p.445-460, set./out., 2014 These new aggregates were formed possibly by the action of biological factors (Silva et al 2013;Martin et al 2012), via the constant supply of the organic material throughout the soil profile, by both the mowing of the interrow Brachiaria sp. and the renewal of the coffee roots, that increase the soil microorganism activity (mycorrhizal fungi, preferentially).…”
Section: Treatmentsmentioning
confidence: 99%
“…Dessa forma, a adubação nitrogenada pode ser adotada com a finalidade de minimizar os efeitos do pisoteio animal, uma vez que uma maior produção de matéria verde reduziria a pressão aplicada pelo peso dos animais na superfície do solo (CARASSAI et al, 2011). Essa prática pode promover, ainda, melhorias na qualidade física do solo, já que proporciona incremento do teor de matéria orgânica e favorece a descompactação do solo por meio do desenvolvimento das raízes (SILVA et al, 2013).…”
Section: Introductionunclassified